The evolution of the first-sale price in commercial fisheries in the inland territorial waters of Romania - Erzsebet Olariu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The policy of the fishing sector in Romania, in terms of commercial fishing, it envisages measures that ensure the sustainable exploitation of living aquatic resources, efficient management, stimulating those who work in this sector to unite in associative forms, the collection of statistical data, inspection and control.The policy on fishing in natural fish habitats is carried out by the National Agency for Fisheries andAquaculture.This paper studies the national average fish prices for the first- sale for commercial fishing in the inland territorial waters. How to change the value of these prices for the years 2016-2020, regarding the species and the quantity. They were used the statistical data were provided by NAFA, and the quality interview. The first- sale prices are established at the first- sale points based on negotiation. The average price of the total catch of fish in Romania from 2016 to 2019 do not show large fluctuations, but in 2020 had an increase of over 30%, compared to 2019, while the amount of fish caught decreased by 25% in 2020 compared to 2019.
Keywords: Q22; Q31; 330; fishery; first-sale price